Detection of porcine bocavirus in Malaysian swine herds - Jacob, Daniel Mohan (2015)
Porcine bocavirus (PBoV), which was first discovered in Swedish pigs in 2009, has since been detected in 11 other countries at the time of writing. As Malaysia is host to a significant swine livestock industry, this study aimed to describe PBoV in local swine herds. Using the convenience sampling method, 11 pigs were sampled from three farms located in the states of Perak and Selangor. Each tissue sample obtained from necropsy were subjected to conventional PCR assay using specific primers designed to target the conserved nonstructural protein 1 (NS1) gene. Based on PCR assay, 10 out of 11 pigs were positive for PBoV. For further confirmation, partial nucleotide sequencing of the NS1 gene was performed, and the sequence compared to reference isolates. In addition, phylogenetic analysis was performed to determine the genetic relationship of Malaysian PBoV strains to reference isolates. Bioinformatics analysis determined that the Malaysian strain was highly similar (95%) to PBoV3 isolated in USA. To further understand PBoV in Malaysia, prevalence study, virus isolation and complete genome sequencing should be performed. In conclusion, Malaysia is the 13th country in the world that has described PBoV in its swine herds by PCR assay and partial sequencing of the NS1 gene.